Indonesian Crude Palm Oil (CPO) Exports Through the Gravity Model Approach - Lilis S Gultom; Nelly MR Sinaga (Postgraduate, University of Mataram, 2023)
Oil palm is one of the plantation crops that provides the largest contribution to Indonesia's foreign exchange with its derivative products in the form of crude palm oil (CPO). The development of CPO consumption as a source of vegetable oil has pushed Indonesia as the largest producer to export CPO to 179 export destination countries in the world and the 10 largest export countries include India, China, Pakistan, the Netherlands, Malaysia, Bangladesh, Egypt, Italy, Spain and Singapore. Indonesia's CPO export volume fluctuates which can disrupt the country's economy. The objectives of this study are: (1) to identify the countries that positively impact Indonesian crude palm oil (CPO) exports among 10 destination countries, namely India, China, Pakistan, the Netherlands, Malaysia, Bangladesh, Egypt, Italy, Spain, and Singapore, (2) to analyse the factors influencing Indonesia's CPO exports to these 10 destination countries, and (3) to examine the impact of geographical distance on Indonesia's CPO exports to these countries. The research was conducted from April to September 2021, using panel data that combines time series and cross-sectional data from 2011 to 2020. The findings indicate that India, China, the Netherlands, and Italy had positive constants, while the remaining six countries had negative constants in terms of Indonesia's CPO exports. The combined effect of Indonesia's gross domestic product (GDP) (X1), geographical distance (X2), and the rupiah exchange rate (X3) significantly increased Indonesia's CPO exports to these 10 destination countries by 73.77%. Geographical distance (X2) had a significant and positive effect, whereas Indonesia's GDP (X1) and the rupiah exchange rate (X3) did not show significant effects and had a negative impact on increasing Indonesia's CPO exports to these destinations